2007
DOI: 10.1111/j.1444-2906.2007.01386.x
|View full text |Cite
|
Sign up to set email alerts
|

Possibility for decreasing of mercury content in bluefin tuna Thunnus orientalis by fish culture

Abstract: The bluefin tuna tested were reared for 22 months from eggs before the beginning of the experiment, and sampling was performed every 3 months over the following year. The experimental results showed that the mercury concentration in the muscle ranged from 0.32 to 0.85 mg/g, which is lower than that found in wild bluefin tuna of a similar size. Increase in the mercury concentration corresponding to the increase in body weight was not shown, and it was quite different with wild bluefin tuna. Furthermore, no sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 25 publications
4
22
2
Order By: Relevance
“…The average muscle tissue THg at the longest time periods (after equilibration) is ∼12 times higher than the THg of the dietary mixture, which illustrates the bioaccumulation factor (THg concentration of PBFT white muscle tissue divided by the weight mean THg concentration of the dietary mixture). The small decreasing trend in THg concentration with time in captivity is consistent with previous studies, which reported THg concentrations in captive and farmed PBFT (Nakao et al, 2007;Lares et al, 2012;Coleman et al, 2015). These studies attributed the reduction in THg concentration to internal biodilution due to growth.…”
Section: Thg Concentrations Of Pbftsupporting
confidence: 81%
“…The average muscle tissue THg at the longest time periods (after equilibration) is ∼12 times higher than the THg of the dietary mixture, which illustrates the bioaccumulation factor (THg concentration of PBFT white muscle tissue divided by the weight mean THg concentration of the dietary mixture). The small decreasing trend in THg concentration with time in captivity is consistent with previous studies, which reported THg concentrations in captive and farmed PBFT (Nakao et al, 2007;Lares et al, 2012;Coleman et al, 2015). These studies attributed the reduction in THg concentration to internal biodilution due to growth.…”
Section: Thg Concentrations Of Pbftsupporting
confidence: 81%
“…This explains the higher mercury level found in the Pacific Ocean. As fish living in environments with high mercury levels have been shown to accumulate more mercury in their tissues than fish exposed to lower levels of mercury [10,17], bioaccumulation of mercury in marine organisms is expected to be higher in the Pacific Ocean. Consequently, the higher mercury levels in the Pacific Ocean, which may be caused by volcanic activity, could be the reason why fish caught in the Pacific Ocean had higher mercury levels than those caught in the Sea of Japan in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Nakao et al [10] suggested that most mercury is included in the protein fraction, making muscle an important tissue to check, rather than internal organs, whose weight is small. For this reason, muscle was sampled for analysis in the abdominal area above the vent of the fish, because mercury is uniformly distributed in fish edible muscle [15].…”
Section: Measurement Of Total Mercury Levelsmentioning
confidence: 99%
See 2 more Smart Citations